2021
DOI: 10.1101/2021.04.23.21255846
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transmission of SARS-CoV-2 within households: a prospective cohort study in the Netherlands and Belgium – Interim results

Abstract: Background: Household transmission studies are useful to obtain granular data on SARS-CoV-2 transmission dynamics and to gain insight into the main determinants. In this interim report we investigated secondary attack rates (SAR) by household and subject characteristics in the Netherlands and Belgium. Methods: Households with a real-time reverse transcription polymerase chain reaction (RT-PCR) confirmed SARS-CoV-2 index case were enrolled <48 hours following report of the positive test result. Daily sympto… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 33 publications
(26 reference statements)
1
17
0
Order By: Relevance
“…Compared with the SAR for 28 studies 12,14,17,27,94 from January to February 2020 (13.4%; 95% CI, 10.7%-16.7%), the SAR was significantly higher for 30 studies 6,7,15,16,19,22,25,26,28,30,[68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86]93 from March to April 2020 (19.4%; 95% CI, 15.2%-24.5%; P = .03) and 15 studies 5,8,10,18,20,21,23,24,29,31,32,35,37,38,40 from July 2020 to March 2021 (31.1%; 95% CI, 22.6%-41.1%; P < .001) but not significantly different from the SAR for 14 studies…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with the SAR for 28 studies 12,14,17,27,94 from January to February 2020 (13.4%; 95% CI, 10.7%-16.7%), the SAR was significantly higher for 30 studies 6,7,15,16,19,22,25,26,28,30,[68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86]93 from March to April 2020 (19.4%; 95% CI, 15.2%-24.5%; P = .03) and 15 studies 5,8,10,18,20,21,23,24,29,31,32,35,37,38,40 from July 2020 to March 2021 (31.1%; 95% CI, 22.6%-41.1%; P < .001) but not significantly different from the SAR for 14 studies…”
Section: Resultsmentioning
confidence: 99%
“…To elucidate factors associated with differences in SAR, we explored attributes of studies from the periods with the lowest and highest household SARs. Among 28 studies 12,14,17,27,94 from January to February 2020 and 15 studies 5,8,10,18,20,21,23,24,29,31,32,35,37,38,40 from July 2020 to March 2021, 6 studies 12,46,54,57,59,62 (21.4%) and 4 studies 8,10,20,23 (25.0%), respectively, reported testing contacts at least twice, 1 study 46 (3.6%) and 3 studies 5,8,23 (18.8%) reported following contacts for longer than 14 days, 1 study 45 (3.6%) and 6 studies 8,23,24,29,37,40 (33.3%) were published as preprints, 21 studies 12,14,27,46,[48][49][50]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding of reduced viral loads also suggests some to-be-validated potential to reduce transmission to household members and other high-risk contacts. In a prospective cohort study conducted in the Netherlands and Belgium, it was shown that secondary transmission within households occurred in 44.4% of the households, mostly very early after the index patient was positive [17]. Moreover, it might be useful for future studies to stratify potential responders and non-responders based on the microbiome (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were asked to use the verum spray or placebo for 14 days, with one week of follow-up, and filled in an online diary via Qualtrics (Qualtrics, Provo, UT, USA) (detailed description in Figure S1). Ten common COVID-19 symptoms were monitored, according to [17]. Different symptom summary scores were compared between the verum and placebo groups, and time to improvement was evaluated based on the timepoint when participants reached their symptomatic tipping point (supplementary methods).…”
Section: Study Proceduresmentioning
confidence: 99%